Reaction Mechanism of H2C2O4 Oxidized by HNO2 via Mn2+ as Catalyst - HAO Shuai;LI Bin;LI Xianjun;LIU Zhanyuan;LIU Min;JIANG Dongmei;XIA Liangshu (Yuanzineng kexue jishu, 2023)
H2C2O4 is widely used in spent fuel reprocessing. For example, in order to recovery plutonium oxalate precipitated mother liquor before returning, it is necessary to reduce the H2C2O4 concentration from 0.1 mol/L to about 10-4 mol/L. Among the methods of H2C2O4 destroyed in waste liquid, the process of H2C2O4 oxidized in nitric acid solution with Mn2+ as a catalyst is the most mature and suitable for industrialization, and its research is very rich. Nitrite plays an important role in destroying oxalic process in the process of H2C2O4 destroyed with Mn2+ as a catalyst in nitric acid solution was mentioned in many past studies. However, the specific reaction chain is still ambiguous and controversial on nitrite oxidation of H2C2O4 with Mn2+ as a catalyst, and the catalytic reaction mechanism is not clear. To solve these issues in the area of post-processing, the optimization of the treatment of the mother liquor of plutonium oxalate precipitation in the Purex process and the acquisition of H2C2O4 deep destruction technology in spent fuel reprocessing are to be benefited. Firstly, sodium nitrite solutions were continuously added into reaction solutions, at the same time the concentration of H2C2O4 in solutions was determined. H2C2O4 is obviously oxidized in the presence of nitrite and Mn2+ in sulfuric acid solutions. Secondly, Mn(Ⅱ) complexed oxalate oxidized to Mn(Ⅲ) with nitrous acid as a oxidant was studied. The results demonstrate that the complexation of Mn2+ with H2C2O4 reduces the reaction activation energy of Mn(Ⅱ) oxidized to Mn(Ⅲ), and MnC2O4 can be oxidized to ［Mn(C2O4)3］3- by nitrous acid. Finally, free radicals and substates in reaction process were detected by EPR’s spin capture technique. H2C2O4 is oxidized to ·OOC—COOH with the Mn(Ⅲ) complexed with itself, and Mn(Ⅲ) is reduced to Mn(Ⅱ). The ·OOC—COOH radicals with poor stability rapidly decompose and release reducing substances in acidic solution, and decomposition of H2C2O4 is completed. With the increase of acidity of nitrous acid, the concentration of HNO3 molecule increases. Thus, the concentration of HNO3 molecule in the solution can no longer be neglected compared with the concentration of nitrous acid. Therefore, when the concentration of nitric acid is more than 6 mol/L, the decomposition rate of H2C2O4 in the nitric acid solution with Mn2+ as a catalyst may be controlled by various reactions, which needs to be further studied.